From rhetoric to practice: a study on the right to accessible and adequate housing in Kenya - (:unkn) unknown (My University, 2015)
The Universal Declaration of Human Rights provides, among other things, that “everyone has the right to an adequate standard of living…including the right to housing.”1 This has been defined by the first Special Rapporteur on adequate housing as, “the right of every woman, man, youth and child to gain and sustain a safe and secure home and community in which to live in peace and dignity.”2 As with other Economic and Social Rights International Law requires the progressive realization of the right, to the maximum of the country’s available resources, in a non-discriminatory manner. Sadly, in many countries in the world, Kenya included, the gap between housing rights rhetoric and realization is extremely broad. A recent report on the right to housing under international law, prepared by the UN, opens by stating that the right to housing is a ‘fundamental human right’, and that it has been recognized by “over 100 constitutions”.3 The reality however remains that despite this constitutional recognition and the central place of this right within the global legal system; well over a billion people are not adequately housed. Millions around the world live in life or health threatening conditions, in overcrowded slums and informal settlements, or in other conditions which do not uphold their human rights and their dignity. Further millions are forcibly evicted, or threatened with forced eviction, from their homes every year.4 This begs the question, what is the value of recognition? Does it translate into actual justiciability for those whose rights are violated? And perhaps more importantly, how are these rights to be adjudicated, especially in developing countries like Kenya where governments neither have the resources nor the ability to provide housing for huge proportions of their populations who live in crippling poverty?
Article
Keywords: Housing; Kenya